INCREASING COLOR QUALITY OF RED EMPEROR SNAPPER Lutjanus sebae SEED THROUGH ENRICHED DIET WITH RED FRUIT Pandanus conoideus OIL AS BETA-CAROTEN SOURCE - Titiek Aslianti; Afifah Nasukha (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Market price of red emperor snapper Lutjanus sebae is often determined by its color performance. Adding beta-carotene on a fish diet would possibly escalate red pigmentation. Oil from a red fruit (Pandanus conoideus, Lam) known as potential beta-carotene source was used as a supplement diets. The dosage of 10, 5, and 0 ml were added to every kg of pellet as the treatment. Three hundred seeds with initial average length of 8.43±0.9 cm and body weight of 13.22±3.9 g were stocked in each of three unit fiberglass tank of 4 m3 seawater (salinity of 33-34). Experiment was conducted during three-month periods. Feeding frequency was twice a day with dosage of 3% of biomass. Monthly monitoring was done to measure the growth rate. Color performance was taken by digital photography at the end of observation and analyzed by conversion methods of color gradation using “Microsoft Adobe Photoshop-8”program. Carotene contents in the diets and fish body was examined. Fed effectivity values were observed by analysis of feed conversion ratio (FCR) and water quality that observed every 3 days. The results showed that the Pandanus conoideus oil as beta-carotene source had a significant role in increasing performance of red emperor snapper color i.e. brighten in red color. Ten ml dosage of Pandanus conoideus oil gave the best color and growth performance with 17.99 cm and 143.10 g for total length and body weight respectively, with 95.67% survival rate.Keywords: Beta-carotene, Color Performance, Red emperor snapper, Red fruit oil.